Targeting lncRNA PSMA3-AS1, a Prognostic Marker, Suppresses Malignant Progression of Oral Squamous Cell Carcinoma. (20th August 2021) - Cao, Xinghua; Luan, Kefeng; Yang, Jie; Huang, Yundong
Abstract : Objective . Oral squamous cell carcinoma (OSCC) represents the most common maxillofacial malignancy. This study elucidated the clinicopathological value and molecular mechanisms of PSMA3 antisense RNA 1 (PSMA3-AS1) in OSCC. Methods . Totally, 135 OSCC patients were recruited. PSMA3-AS1 expression and its prognostic value were assessed in this cohort. si-PSMA3-AS1 was transfected into HN4 and CAL-27 OSCC cells. Then, cell proliferation was evaluated by CCK-8, colony formation, and EdU staining. Migration and invasion were investigated through wound healing, transwell, and western blot. The PSMA3-AS1/miR-136-5p and miR-136-5p/FN1 interactions were validated by dual luciferase report, real-time quantitative polymerase chain reaction (RT-qPCR), and western blot. Results . PSMA3-AS1 upregulation was determined in OSCC tissues. The upregulation indicated pessimistic patients' outcomes. Multivariate Cox regression analyses confirmed PSMA3-AS1 as an independent prognostic indicator. Its upregulation was also found in OSCC cells. Under transfection with si-PSMA3-AS1, proliferation, migration, and invasion were all restrained in HN4 and CAL-27 OSCC cells. Furthermore, its knockdown induced the increase in E-cadherin expression and the reduction in N-cadherin and Vimentin expression. PSMA3-AS1 was a sponge of miR-136-5p. Mutual inhibition was found between two and the interactions were confirmed by dual luciferase report. It was confirmed that FN1 was a target of miR-136-5p. FN1 expression was increased by miR-136-5p inhibitors, which was lessened by si-PSMA3-AS1 cotransfection. Conclusion . Collectively, PSMA3-AS1 as a risk factor facilitated malignant behaviors of OSCC cells, related to the miR-136-5p/FN1 axis. Hence, PSMA3-AS1 as a potential therapeutic target for OSCC deserved further exploration.